(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
The Special Allocation Fund (DAK) is part of the Special Transfer Fund (DTK) allocated by the central government to support basic social ser-vices in the regions. This program aims to assist areas in providing social infrastructure, particularly for vulnerable groups such as the poor, elder-ly, children, and people with disabilities, to reduce socio-economic dispari-ties among regions in Indonesia. Since it was proposed in 2020, imple-menting the Physical DAK in the social sector has faced various challeng-es, primarily due to the COVID-19 pandemic, which has led to budget re-focusing and reallocation. The impact of the pandemic forced the govern-ment to make budget policy changes, resulting in suboptimal program im-plementation in many regions. This study employs descriptive analysis methods to examine the planning, implementation, and evaluation of the Physical DAK in the social sector during 2020–2024. The findings indi-cate that despite limitations in implementation due to the pandemic, the Physical DAK in the Social Sector has significantly contributed to sup-porting the fulfillment of Minimum Service Standards (SPM) for Social Services in the regions. Several identified challenges include low budget allocation from the Regional Budget (APBD) for social services, more ef-fective coordination between central and regional governments, and more flexible policies to address crises. This study’s recommendations include optimizing the allocation and use of the Physical DAK in the social sector, enhancing the capacity of local governments in fund management, and strengthening continuous evaluation mechanisms to ensure effective budget usage. With adaptive policies, the sustainability of the physical DAK in the social sector is expected to support equitable access to social services across Indonesia.